A copper calcium nickel titanate composite fiber and its preparation method and application in polyvinylidene fluoride composite film

By using nickel nanoparticles to embed the composite fiber of copper calcium titanate fibers in electrostatic film capacitors and performing high-temperature and strong magnetic field treatment, the low dielectric constant and loss factor under high-temperature and high-frequency conditions are solved. The problem of enlargement is achieved by achieving composite materials with high dielectric constant and low loss factor.

CN116516523BActive Publication Date: 2025-02-07CHANGZHOU INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310598055.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-25
Publication Date
2025-02-07
Estimated Expiration
2043-05-25

AI Technical Summary

Technical Problem

In the high temperature and high frequency conditions of existing electrostatic film capacitors, the dielectric constant of ceramic/polymer composites is not high and the dielectric loss is significantly increased.

Method used

The composite fibers embedded in the copper calcium titanate fibers were synthesized by one-step electrospinning method, and then mixed with the polyvinylidene fluoride polymer substrate solution to form a film, and then carried out high-temperature and strong magnetic field magnetoordering treatment. Form a high polarization response copper calcium nickel titanate/polyvinylidene fluoride composite material.

Benefits of technology

In the high temperature range of 90-130°C and under the high frequency conditions of 10K-1MHz, the composite material has a high dielectric constant of 20.6-23.3 and a low loss factor of 0.056-0.204, which significantly improves the dielectric constant and reduces the loss factor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116516523B_ABST
    Figure CN116516523B_ABST
Patent Text Reader

Abstract

The present invention discloses a copper calcium nickel titanate composite fiber and a preparation method thereof and an application thereof in a polyvinylidene fluoride based composite film, belonging to the technical field of polymer composite materials and their preparation. The present invention solves the problem that the dielectric constant of the ceramic / polymer composite material of the existing electrostatic film capacitor is not high under high temperature and high frequency conditions, and the dielectric loss is significantly increased due to the high temperature and high frequency environment. The present invention adopts a one-step electrostatic spinning method to synthesize a composite fiber in which nickel nanoparticles are embedded in the copper calcium titanate fiber, and after mixing with a polyvinylidene fluoride polymer substrate solution, the composite fiber is thermoset to form a film, and a high temperature and strong magnetic field is used to perform magnetic ordering treatment on the polyvinylidene fluoride based composite film to form a composite material with a high polarization response. The obtained composite material has a high dielectric constant of 20.6 to 23.3 and a low loss factor of 0.056 to 0.204 under extreme test conditions of a high temperature range of 90 to 130°C and a high frequency condition of 10K to 1MHz.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a copper calcium nickel titanate composite fiber and a preparation method thereof and application thereof in a polyvinylidene fluoride composite film, and in particular to a polyvinylidene fluoride ordered ceramic fiber composite material with high dielectric constant and low loss factor under high temperature environment and a preparation method thereof, belonging to the technical field of polymer composite materials and preparation thereof. Background Art

[0002] Film capacitors are widely used in electronic systems, electric vehicle onboard charging systems, and wind power conversion devices due to their excellent high temperature and high voltage resistance, good reliability, and overvoltage self-healing ability. Especially in the fields of new energy, wind, solar, storage, and electric vehicles, there is considerable incremental demand. As an upstream and midstream component of the power electronics industry, they are being more widely used and the market is expanding rapidly with the rapid development of the new energy market.

[0003] As the key dielectric material of film capacitors, the performance of the plastic base film is determined by its electrical properties and lifespan, especially the dielectric constant, dielectric loss, temperature resistance and flexibility of the base material. The high dielectric constant, low dielectric loss, high temperature resistance and good flexibility of the base material have always been required for the development of film capacitor dielectrics for power conversion devices. Polymer materials have the characteristics of easy processing, good flexibility and good insulation performance, but their dielectric constant is low (≤10). Adding high dielectric constant fillers to them can make up for the disadvantage of low dielectric constant. However, although adding high volume fraction (≥20%) of ceramic fillers can effectively improve their dielectric constant, their dielectric loss (≥0.5) is too large, and low-content ceramics cannot effectively improve the dielectric constant value of polymer dielectrics. For this reason, adding metallic fillers such as Ag, Fe and other third-phase materials in ceramic / polymer composites can reduce the amount of ceramics to obtain a higher dielectric constant, but it inevitably increases the dielectric loss, which is caused by the excessive loss of metallic additives in the polymer matrix. Although adding high dielectric ceramics or metallic additives can improve the high dielectric constant of polymer composite dielectrics, as dielectric materials for capacitors used as power conversion elements, under extreme conditions of high temperature environments (≥85°C) and high frequency conditions (≥10KHz), the dielectric constant of such polymer composite materials becomes low (≤15), and their dielectric loss increases significantly due to high temperature and high frequency environments (≥0.7). For this reason, it is urgent to develop polymer composite materials with high dielectric constants and low dielectric losses for electrostatic film capacitors under extreme conditions of high temperature and high frequency. Summary of the invention

[0004] In order to solve the problem that the dielectric constant of the ceramic / polymer composite material of the existing electrostatic film capacitor is not high (≤15) under high temperature and high frequency (≥85°C, ≥10KHz) conditions, and the dielectric loss is significantly increased (≥0.7) due to the high temperature and high frequency environment, the present invention provides a copper calcium nickel titanate composite fiber and a preparation method thereof and an application in a polyvinylidene fluoride based composite film.

[0005] The technical solution of the present invention:

[0006] One of the purposes of the present invention is to provide a method for preparing copper calcium nickel titanate composite fiber, the method comprising the following steps:

[0007] (1) mixing ethanol and acetic acid evenly, adding copper acetate and calcium nitrate, and stirring until completely dissolved to obtain a Ca / Cu / Ti mixed solution;

[0008] (2) adding nickel powder to the Ca / Cu / Ti mixed solution, stirring evenly, slowly adding polyvinyl pyrrolidone, and continuing to stir until completely dissolved to obtain a precursor solution;

[0009] (3) transferring the precursor solution into a syringe and performing electrospinning to obtain primary fibers;

[0010] (4) drying the as-spun fibers and placing them in a muffle furnace for annealing treatment to obtain copper calcium nickel titanate composite fibers.

[0011] It is further defined that the stirring speed in (1) is 100 to 150 r / min and the stirring time is 10 to 30 min.

[0012] It is further defined that the particle size of the nickel powder in (2) is 5 to 50 nm.

[0013] It is further defined that the addition rate of polyvinyl pyrrolidone in (2) is 0.1 to 0.3 g / min.

[0014] It is further defined that the electrospinning process in (3) is as follows: the spinning receiving distance is 16 to 20 cm, the spinning voltage is 12 to 16 kV, and the propulsion rate is 0.2 to 0.4 mL / min.

[0015] It is further defined that the annealing heat treatment in (4) is as follows: a heating rate of 1 to 3°C / min, a temperature of 800 to 980°C, and an annealing holding time of 1 to 2h.

[0016] It is further defined that the annealing heat treatment in (4) is as follows: heating rate 1.5°C / min, temperature 900°C, annealing holding time 1h.

[0017] It is further defined that the mass volume ratio of ethanol, acetic acid, copper acetate, calcium nitrate, nickel powder and polyvinyl pyrrolidone is 10 mL: 0.2 mL: 0.264 g: 0.104 g: 0.0047-0.0258 g: 0.73 g.

[0018] It is further defined that the mass volume ratio of ethanol, acetic acid, copper acetate, calcium nitrate, nickel powder and polyvinyl pyrrolidone is 10 mL: 0.2 mL: 0.264 g: 0.104 g: 0.0141 g: 0.73 g.

[0019] The second object of the present invention is to provide an application of the copper calcium nickel titanate composite fiber prepared by the above method, specifically for preparing a polyvinylidene fluoride based composite film.

[0020] The third object of the present invention is to provide a method for preparing the above-mentioned polyvinylidene fluoride based composite film, the method comprising the following steps:

[0021] S1, mixing copper calcium nickel titanate composite fiber and N,N-dimethylformamide and then ultrasonically treating the mixture to obtain a dispersion;

[0022] S2, adding polyvinylidene fluoride to the dispersion, stirring evenly and then letting it stand to obtain a viscous mixed solution;

[0023] S3, coating the viscous mixed solution on a glass plate to obtain a wet film;

[0024] S4, placing the wet film in an oven for curing treatment to obtain a dry film, and then placing the cured dry film in the center of a constant electromagnet for magnetron treatment, with the magnetic field direction perpendicular to the film, the upper and lower magnetic poles having an ambient temperature of 150°C, a magnetic field strength of 1.0 to 1.5 T, and a magnetic field treatment time of 30 to 60 min to obtain a polyvinylidene fluoride based composite film.

[0025] It is further defined that the ultrasonic treatment power in S1 is 150 to 200 W, and the time is 10 to 30 min.

[0026] It is further defined that the stirring speed in S2 is 200-300 r / min and the time is 2-3 h.

[0027] It is further defined that the standing time in S2 is 5 to 7 hours.

[0028] It is further defined that the addition rate of polyvinylidene fluoride in S2 is 10 to 50 mg / min.

[0029] It is further defined that the volume ratio of the polymer to the additive in the viscous mixed liquid in S2 is (5.25-8):1.

[0030] It is further defined that the volume ratio of the polymer to the additive in the viscous mixed liquid in S2 is 5.67:1.

[0031] It is further defined that in S3, the viscous mixed liquid is coated on the glass plate using a scraper, the scraper moves at a speed of 40 to 60 cm / min, and the moving time is 10 to 45 s.

[0032] It is further defined that the curing treatment temperature in S4 is 50-80° C. and the time is 6-10 hours.

[0033] It is further defined that the magnetron treatment in S4 is as follows: the direction of the magnetic field is perpendicular to the film, the ambient temperature of the upper and lower magnetic poles is 150°C, the magnetic field strength is 1.5T, and the magnetic field treatment time is 30min.

[0034] Beneficial effects:

[0035] (1) The present invention adopts a one-step electrospinning method to synthesize a composite fiber in which nickel nanoparticles are embedded in copper calcium titanate fibers, which is mixed with a polyvinylidene fluoride polymer substrate solution and then thermally cured to form a film. A high temperature and strong magnetic field is used to perform magnetically induced ordering on the polyvinylidene fluoride-based composite film to form a copper calcium nickel titanate / polyvinylidene fluoride composite material with a high polarization response.

[0036] (2) The copper calcium nickel titanate / polyvinylidene fluoride composite material prepared by the present invention has a high dielectric constant of 20.6 to 23.3 under extreme test conditions of a high temperature range of 90 to 130°C and a high frequency working condition of 10K to 1MHz, which is 131.5% to 137.8% higher than that of pure polyvinylidene fluoride material, and has a low loss factor of 0.056 to 0.204.

[0037] (3) The preparation method provided by the present invention requires low raw material cost and simple preparation process, and provides a new method for the development of polymer-based composite materials with high dielectric constant and low loss factor under high temperature and high frequency conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is the XRD pattern of the copper calcium nickel titanate composite fiber obtained in Example 1;

[0039] Figure 2 TEM photo and EDX element distribution map of the copper calcium nickel titanate composite fiber obtained in Example 1;

[0040] Figure 3 This is a pie chart of EDX element distribution of the copper calcium nickel titanate composite fiber obtained in Example 1;

[0041] Figure 4 This is a cross-sectional SEM image of the polyvinylidene fluoride based composite membrane P / CN-1.0T obtained in Example 2;

[0042] Figure 5 XRD comparison curves of polyvinylidene fluoride based composite films obtained in different embodiments;

[0043] Figure 6 A comparison chart of dielectric constants of polyvinylidene fluoride based composite films obtained in different embodiments at a high temperature of 130° C. and a high frequency of 10 KHz;

[0044] Figure 7 The relationship between the dielectric constant and loss factor of the P substrate film obtained in Comparative Example 1 and the frequency;

[0045] Figure 8 The relationship between the dielectric constant and loss factor of the P / CN composite film obtained in Comparative Example 2 and the frequency;

[0046] Fig. 9 The relationship between the dielectric constant and loss factor of the P / CN-1.0T composite film obtained in Example 2 and the frequency;

[0047] Fig.10 The relationship between the dielectric constant and loss factor of the P / CN-1.5T composite film obtained in Example 3 and the frequency;

[0048] Fig.11 The graph is a comparative relationship between the imaginary part of the electric modulus and the frequency of the polyvinylidene fluoride based composite films obtained in different embodiments at a high temperature of 140°C;

[0049] Fig.12 It is a comparative relationship diagram between the test value and the fitting value of the logarithm of the peak frequency of the imaginary part of the electric modulus and the inverse of the temperature of the polyvinylidene fluoride based composite film obtained in different embodiments. DETAILED DESCRIPTION

[0050] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0051] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0052] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0053] The ethanol, acetic acid, copper acetate, calcium nitrate, and N,N-dimethylformamide used in the following examples were provided by China National Pharmaceutical Chemical Reagent Co., Ltd.; the nickel powder had a size of 5 to 50 nm, was spherical, and granular; polyvinyl pyrrolidone was provided by Shanghai Aladdin Biotechnology Co., Ltd.; and polyvinylidene fluoride was provided by Shanghai San Ai Fu New Material Technology Co., Ltd.

[0054] Example 1

[0055] The specific operation process of preparing copper calcium nickel titanate composite fiber CN in this embodiment is as follows:

[0056] First, add 0.2 mL of acetic acid to a beaker containing 10 mL of ethanol and stir magnetically for 30 min until uniformly mixed at a stirring speed of 200 r / min.

[0057] Secondly, 0.264 g of copper acetate and 0.104 g of calcium nitrate were added respectively, and magnetic stirring was performed for 30 min at a stirring speed of 200 r / min until they were completely dissolved to obtain a Ca / Cu / Ti mixed solution;

[0058] Next, nickel powder was added to the Ca / Cu / Ti mixed solution; wherein the nickel powder had a size of 25 nm, was spherical, and was granular, and had a mass of 0.0141 g; the magnetic stirring was continued for 30 min at a stirring speed of 200 r / min;

[0059] Then, 0.73 g of polyvinyl pyrrolidone powder was slowly added to the Ca / Cu / Ti / Ni mixed solution at a rate of 0.1 g / min, and magnetically stirred for 8 h at a rate of 300 r / min until it was completely dissolved to obtain a Ca / Cu / Ti / Ni / PVP precursor solution;

[0060] Next, the precursor solution was transferred into a syringe, and the spinning receiving distance was set to 18 cm, the spinning voltage was 14 kV, and the propulsion rate was 0.35 mL / min. After electrospinning treatment, a nascent fiber sample was obtained;

[0061] Finally, the as-spun fiber was placed in a muffle furnace for annealing heat treatment at a calcination temperature of 900°C, a heating rate of 1.5°C / min, and an annealing holding time of 1h to obtain copper calcium nickel titanate composite fiber (marked CN).

[0062] The XRD test results of CN prepared in this example are as follows Figure 1 As shown by Figure 1 It can be seen that CN fibers are mainly CaCu3Ti4O 12Phase (conforming to standard comparison card PDF#75-2188), but no Ni phase was detected, which may be due to the fact that the preparation method adopted in the present invention enables nickel nanoparticles to be embedded in the interior of copper calcium titanate fibers and the nickel content is very low. In addition, it is found that the XRD spectrum of CN fibers shows a TiO2 phase diffraction peak (conforming to standard comparison card PDF#21-1276), indicating that CN fibers are rich in TiO2 phase components.

[0063] The TEM image and EDX element distribution map of CN prepared in this example are shown in Figure 2 As shown, a is a TEM photo, b is Ca element, c is Cu element, d is Ti element, e is O element, and f is Ni element. Figure 2 It can be seen from a that the CN fiber has a non-smooth surface and is composed of polycrystalline particles. The fiber contains extremely small particles uniformly embedded in it, forming a multi-phase composite structure. The short axis diameter of the CN fiber is about 900nm. Figure 2 From b to 2f, we can see that the CN fiber contains Ca, Cu, Ti, O and Ni elements. Through the different color contrasts formed by the local distribution of each element, it is found that the fiber is rich in granular substances formed by Ti and O, specifically TiO2 particles; and the Ni element is evenly distributed inside the fiber, indicating that the nickel particles are evenly embedded in the fiber. Further quantitative EDS results of CN fiber, such as Figure 3 As shown in FIG. 1 , the atomic percentage of nickel in the CN fiber is 0.02%, and the nickel element component is very small; and according to the atomic percentages of Ca, Cu, Ti and O, it can be known that the main copper titanate calcium phase component in the CN fiber prepared by the present invention is CaCu3Ti4O 12 .

[0064] Example 2

[0065] The CN prepared in Example 1 was mixed with polyvinylidene fluoride to form a film, and the P / CN-1.5T composite film with an oriented structure was obtained by curing and magnetron treatment. The specific operation process is as follows:

[0066] First, the CN composite fiber prepared in Example 1 was added to a three-necked bottle containing 19 mL of N,N-dimethylformamide, and ultrasonically treated for 20 min at an ultrasonic power of 250 W. Then, polyvinylidene fluoride powder was added at an addition rate of 30 mg / min, and the volume ratio of polyvinylidene fluoride to fiber was 5.67:1. The mixture was stirred at a speed of 300 r / min for 2.5 h, and then allowed to stand for 6 h to obtain a viscous blend solution.

[0067] Then, the viscous blended solution was poured onto a clean glass plate, and a scraper was moved at a uniform speed for coating, the scraper moving speed was 45 cm / min, and the moving time was 20 s to obtain a coated wet film; finally, the coated wet film was placed in an oven for thermal curing, the oven temperature was 80° C., and the constant temperature time was 6 h to obtain a polyvinylidene fluoride-based composite film (marked P / CN);

[0068] Finally, the P / CN composite film was placed at the center of the magnetic pole of a constant electromagnet, the magnetic field direction was set perpendicular to the film, the upper and lower magnetic pole ambient temperature was 150°C, the magnetic field strength was 1.0T, and the magnetic field treatment time was 40min to obtain a magnetically ordered polyvinylidene fluoride based composite film (marked P / CN-1.0T).

[0069] The cross-sectional SEM photograph of the P / CN-1.0T composite membrane obtained in this example is shown in FIG. Figure 4 As shown by Figure 4 It can be seen that the CN fibers are arranged in an ordered manner in the polyvinylidene fluoride matrix. The CN fibers are oriented along the direction perpendicular to the magnetic field, that is, the direction of the membrane plane. The 1.0T strong magnetic field in the 150°C matrix melting environment magnetizes the CN fibers, causing them to have ordered magnetic domains, generating magnetic torque and rotating. In addition, under the action of the 40min magnetization time, the CN fibers move again, resulting in the formation of an ordered structure of the oriented P / CN-1.0T composite film.

[0070] The relationship between the dielectric constant and loss factor of the P / CN-1.0T composite film obtained in this example and the frequency is shown in the figure below: Fig. 9 As shown by Fig. 9 It can be seen that the dielectric constant of the P / CN-1.0T composite film is less dependent on frequency and temperature, showing a certain degree of stability. The dielectric constant value of the P / CN-1.0T composite film in the high temperature range at a high frequency of 10KHz is 21.0-23.0, which is 134.7%-136.0% and 65.4%-66.7% higher than that of the pure P substrate and the P / CN composite film, respectively. In addition, the loss factor of the P / CN-1.0T composite film in the high temperature range at a high frequency of 10KHz is 0.106-0.426, which is 5.6% higher than that of the pure P substrate film at a high temperature of 90°C, and 3% lower than that of the pure P substrate film at a high temperature of 140°C, showing the superior high dielectric constant and low loss factor characteristics of the composite film under the magnetically ordered structure of the 1.0T magnetic field.

[0071] Example 3

[0072] The present embodiment is different from the embodiment 2 in that the magnetic field strength is 1.5 T, and the other process steps and parameter settings are the same as those in the embodiment 2, thereby obtaining a magnetically ordered polyvinylidene fluoride based composite film (labeled as P / CN-1.5T).

[0073] The relationship between the dielectric constant and loss factor of the P / CN-1.5T composite film obtained in this example and the frequency is shown in the figure Fig.10 As shown by Fig.10 It can be seen that the dielectric constant value of the P / CN-1.5T composite film in the high temperature range under the 10KHz high frequency test is 20.6-23.3, which is 131.5%-137.8% and 62.2%-68.8% higher than that of the pure P substrate film and the P / CN composite film, respectively. In addition, the loss factor of the P / CN-1.5T composite film in the high temperature range under the 10KHz high frequency is 0.121-0.519, showing a lower loss factor. It can be seen that the ordered structure of the P / CN-T composite film caused by increasing the magnetic field strength to 1.5T has significantly improved dielectric constant characteristics and a lower loss factor.

[0074] Comparative Example 1

[0075] The specific operation process of preparing the pure polyvinylidene fluoride substrate film P in this comparative example is as follows:

[0076] First, add polyvinylidene fluoride powder to a three-necked flask containing 19 mL of N,N-dimethylformamide at a rate of 30 mg / min, stir electrically at 300 r / min for 2.5 h, and then let stand for 6 h to obtain a viscous solution;

[0077] Then, pour the viscous solution onto a clean glass plate and apply the film with a scraper moving at a constant speed of 45 cm / min for 20 s to obtain a coated wet film.

[0078] Finally, the coated wet film was placed in an oven for thermal curing treatment at a temperature of 80° C. for 6 h, thereby obtaining a pure polyvinylidene fluoride substrate film (marked P).

[0079] The relationship between the dielectric constant and loss factor of the P substrate film obtained in this embodiment and the frequency is shown in the figure below: Figure 7 As shown, a is the dielectric constant and b is the loss factor. Figure 7 It can be seen that the dielectric constant is 8.9-9.8 under the 10KHz high frequency test, which decreases with the increase of frequency and increases with the increase of temperature. The loss factor of the P substrate film increases with the temperature from 90℃ to 140℃, and the loss factor at 10KHz high frequency is 0.1-0.438. It can be seen that the high temperature and high frequency dielectric constant of pure polyvinylidene fluoride substrate is less than 10, and the loss factor is above 0.4.

[0080] Comparative Example 2

[0081] The specific operation process of preparing the polyvinylidene fluoride composite film P / CN in this comparative example is as follows:

[0082] First, the CN composite fiber prepared in Example 1 was added to a three-necked bottle containing 19 mL of N,N-dimethylformamide, and ultrasonically treated for 20 min at an ultrasonic power of 250 W. Then, polyvinylidene fluoride powder was added at an addition rate of 30 mg / min, and the volume ratio of polyvinylidene fluoride to fiber was 5.67:1. The mixture was stirred at a speed of 300 r / min for 2.5 h, and then allowed to stand for 6 h to obtain a viscous blend solution.

[0083] Then, the viscous blended solution was poured onto a clean glass plate, and the scraper was moved at a constant speed of 45 cm / min for 20 s to obtain a coated wet film; finally, the coated wet film was placed in an oven for thermal curing at 80°C for 6 h to obtain a polyvinylidene fluoride-based composite film (marked P / CN).

[0084] The relationship between the dielectric constant and loss factor of the P / CN composite film obtained in this embodiment and the frequency is shown in the figure Figure 8 As shown, a is the dielectric constant and b is the loss factor. Figure 8 It can be seen that when the volume ratio of polyvinylidene fluoride to fiber is 5.67:1, the dielectric constant of the P / CN composite film in the high temperature range at 10KHz high frequency is 12.7~13.8, which is only 40.8%~42.7% higher than that of the pure P substrate film; and its dielectric constant has a strong dependence on frequency and temperature, decreasing with increasing frequency and increasing with increasing temperature. The loss factor of the P / CN composite film in the high temperature range at 10KHz high frequency is 0.103~0.444, which is 1.4%~3% higher than that of the pure P substrate film; and its loss factor decreases with increasing frequency and increases with increasing temperature, and has a strong dependence on temperature and frequency. It can be seen that the composite film in which CN fibers are randomly distributed in the P substrate has a low degree of improvement in the dielectric constant, but still has a low loss factor.

[0085] The XRD comparison spectra of the polyvinylidene fluoride composite films obtained in Example 2, Example 3 and Comparative Example are shown in FIG. Figure 5 As shown by Figure 5 It can be seen that the γ-PVDF crystal phase diffraction peak of the polyvinylidene fluoride substrate of the composite film after magnetic field ordering treatment is enhanced, such as the γ phase (022) crystal plane at a diffraction angle of 26.7°; and the phase structure of the CN fiber is not destroyed in the matrix. In addition, the CN phase diffraction peak of the composite material obtained in Example 3 is weakened, which is related to the orientation behavior of the CN fiber under the 1.5T strong magnetic field.

[0086] Comparison of dielectric constants of polyvinylidene fluoride composite films obtained in Example 2, Example 3, Comparative Example 1 and Comparative Example 2 at 130°C and 10KHz Figure 6 As shown by Figure 6It can be seen that under the conditions of high temperature of 130°C and high frequency of 10KHz, the dielectric constant of the P substrate film obtained in Comparative Example 1 is only 9.8, the dielectric constant of the P / CN composite film obtained in Comparative Example 2 is 13.8, and the dielectric constant of the P / CN-1.0T composite film ordered by applying a 1.0T magnetic field is 23, which is 2.35 times that of the P substrate film; further, the dielectric constant of the P / CN-1.5T composite film ordered by applying a 1.5T magnetic field is 23.3, which is 137.8% higher than that of the P substrate film. It can be seen that the magnetically ordered P / CN-T composite film of the present invention can significantly improve its dielectric constant value.

[0087] The comparison relationship between the imaginary part of the electric modulus and the frequency of the polyvinylidene fluoride composite film obtained in Example 2, Example 3, Comparative Example 1 and Comparative Example 2 at a high temperature of 140°C is shown in the figure below: Fig.11 As shown by Fig.11 It can be seen that the imaginary part of the electric modulus of the P / CN and P / CN-T composite films shows a relaxation polarization peak in the high-frequency range of 1K~10KHz, which is lower than the intensity of the pure P substrate. The relaxation peak intensity of the P / CN-T composite film under the magnetically ordered structure is the lowest and the width is larger, indicating that the magnetically ordered structure further enhances the interface polarization of the P / CN-T composite film, thereby increasing the dielectric constant of the composite film.

[0088] The comparison relationship between the test value and the fitting value of the logarithm of the peak frequency of the imaginary part of the electric modulus and the inverse of the temperature of the polyvinylidene fluoride composite film obtained in Example 2, Example 3, Comparative Example 1 and Comparative Example 2 is as follows: Fig.12 As shown by Fig.12 It can be seen that the logarithm of the peak frequency of the imaginary part of the electric modulus of the composite film is linearly related to the inverse of the temperature, and the results of fitting using the Arrhenius formula are in good agreement with the test values; according to the fitted activation energy values, it can be seen that the activation energies of the 1.0T and 1.5T magnetically ordered P / CN-T composite films obtained in Examples 2 and 3 are smaller than those of the pure P substrate film and the P / CN composite film, indicating that their interface polarization is large, so the magnetically ordered treatment can significantly enhance the interface polarization response in the composite system, thereby improving the dielectric constant value of the composite film.

[0089] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a polyvinylidene fluoride-based composite film, characterized in that: include: S1, mixing copper calcium nickel titanate composite fiber and N,N-dimethylformamide and then ultrasonically treating the mixture to obtain a dispersion; S2, adding polyvinylidene fluoride to the dispersion, stirring evenly and then letting it stand to obtain a viscous mixed solution; S3, coating the viscous mixed solution on a glass plate to obtain a wet film; S4, placing the wet film in an oven for curing to obtain a dry film, and then placing the cured dry film in the center of a constant electromagnet for magnetron treatment, with the magnetic field direction perpendicular to the film, the upper and lower magnetic poles having an ambient temperature of 150°C, a magnetic field strength of 1.0-1.5T, and a magnetic field treatment time of 30-60min, to obtain a polyvinylidene fluoride composite film; The preparation method of the copper calcium nickel titanate composite fiber comprises: (1) Evenly mix ethanol and acetic acid, then add copper acetate, calcium nitrate and titanium source, and stir until completely dissolved to obtain a Ca / Cu / Ti mixed solution; (2) Add nickel powder to the Ca / Cu / Ti mixed solution, stir evenly, then slowly add polyvinyl pyrrolidone and continue stirring until completely dissolved to obtain a precursor solution; (3) transferring the precursor solution into a syringe and performing electrospinning to obtain primary fibers; (4) Drying the as-spun fibers and placing them in a muffle furnace for annealing treatment to obtain copper calcium nickel titanate composite fibers.

2. The method for preparing a polyvinylidene fluoride-based composite film according to claim 1, characterized in that: (2) The particle size of the medium nickel powder is 5~50nm.

3. The method for preparing a polyvinylidene fluoride-based composite film according to claim 1, characterized in that: (2) The addition rate of polyvinyl pyrrolidone is 0.1~0.3g / min.

4. The method for preparing a polyvinylidene fluoride-based composite film according to claim 1, characterized in that: (3) The electrospinning process is as follows: the spinning receiving distance is 16~20cm, the spinning voltage is 12~16kV, and the propulsion rate is 0.2~0.4mL / min.

5. The method for preparing a polyvinylidene fluoride-based composite film according to claim 1, characterized in that: (4) The intermediate annealing heat treatment is as follows: heating rate 1~3℃ / min, temperature 800~980℃, annealing holding time 1~2h.

6. The method for preparing a polyvinylidene fluoride-based composite film according to claim 1, characterized in that: The volume ratio of polyvinylidene fluoride to copper calcium nickel titanate composite fiber in the viscous mixed liquid is (5.25~8):

1.

7. The method for preparing a polyvinylidene fluoride-based composite film according to claim 6, characterized in that: The volume ratio of polyvinylidene fluoride to copper calcium nickel titanate composite fiber in the viscous mixed liquid is 5.67:

1.

8. The method for preparing a polyvinylidene fluoride-based composite film according to claim 1, characterized in that: The magnetron treatment is as follows: the direction of the magnetic field is perpendicular to the film, the ambient temperature of the upper and lower magnetic poles is 150°C, the magnetic field intensity is 1.5T, and the magnetic field treatment time is 30min.

Citation Information

Patent Citations

  • CaCu3Ti4O12 micro nano sized fiber and its preparation method

    CN102515744A

  • Dielectric material of magnetic control energy storage capacitor and preparation method of dielectric material

    CN106699167A